2023
DOI: 10.35848/1347-4065/acfde6
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial α-Ta (110) film on a-plane sapphire substrate for superconducting qubits on wafer scale

Boyi Zhou,
Lina Yang,
Tao Wang
et al.

Abstract: Realization of practical superconducting quantum computing requires many qubits of long coherence time. Compared to the commonly used Ta deposited on c-plane sapphire, which occasionally form α-Ta (111) grains and β-tantalum grains, high quality Ta (110) film can grow epitaxial on a-plane sapphire because of the atomic relationships at the interface. Well-ordered α-Ta (110) film on wafer-scale a-plane sapphire has been prepared. The film exhibits high residual resistance ratio. Transmon qubits fabricated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…To demonstrate real quantum advantage, the quality and quantity of qubits need to increase simultaneously. In recent years, the coherence time (T 1 ) of Transmon qubits on plane surface has increased to hundreds of microseconds due to the improvement of material quality and fabrication methods [3][4][5][6][7] . In 2020, A. P. M. Place et al reported coherence time of exceeding 0.3 ms for the Transmon fabricated with alpha-phase tantalum lms 8 .…”
Section: Introductionmentioning
confidence: 99%
“…To demonstrate real quantum advantage, the quality and quantity of qubits need to increase simultaneously. In recent years, the coherence time (T 1 ) of Transmon qubits on plane surface has increased to hundreds of microseconds due to the improvement of material quality and fabrication methods [3][4][5][6][7] . In 2020, A. P. M. Place et al reported coherence time of exceeding 0.3 ms for the Transmon fabricated with alpha-phase tantalum lms 8 .…”
Section: Introductionmentioning
confidence: 99%